Desenho como uma criança de 5 anos : traços e traumas na formação de educadoras de infância-professoras do primeiro ciclo - Sousa, Ana, 1980- (2018)
This article focuses on a teaching experience with preservice early childhood educators and primary teachers, in order to bring them closer to the visual arts, with which they generally feel less confident. In it, we share two assignments that we have presented to them, concluding that, confronting their fears and getting involved in the artistic process has helped them to better understand this area of human knowledge, thus discovering meaning(s) for its learning in schools